Assessing the Efficacy of Immersive VR/AR Training Versus Conventional Simulation in Enhancing Clinical Skills and Retention Among Medical Students - Abeer Anjum, Remsha Mustafa, Irum Naz, Khizar Ansar Malik, Danish Ali, Ahsan Rashid Ghumman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Virtual and Augmented Reality (VR/AR) technologies represent an innovative approach to medical education in the context of improving the acquisition and retention of clinical skills. In this study, immersion VR/AR training was compared to conventional simulation-based training of medical students to determine whether immersive VR/AR training can improve immediate and long-term clinical competence at a higher level than conventional simulation-based methods. Methods: Therefore, in a prospective, randomized controlled trial, n=120 Pakistani medical students were randomly assigned to a control group (conventional simulation) or a VR/AR intervention group. Age, gender, year of study, accommodation type, cumulative GPA, and prior simulation training experience were collected as a comprehensive baseline demographic data. The Objective Structured Clinical Examinations (OSCEs) to assess the clinical skills were performed immediately after training and at a three-month follow-up. Confidence in performing clinical tasks was determined with a validated 5-point Likert scale questionnaire. Results obtained were statistically analyzed by the independent and paired t-tests with p < 0.05 as a significance level. Results: Immediate OSCE scores were significantly higher in the VR/AR group (88.3 ± 4.5 vs. 82.1 ± 5.2, p < 0.001) than the control group. The VR/AR group also showed superior performance in OSCE score, which was maintained at 85.2 ± 5.0 at 3 months vs. 78.4 ± 6.1 at 3 months in the control group (p < 0.001). Immediately post training and at three months, performance in the VR/AR group was also significantly higher than in the control group (4.6 ± 0.3 vs. 4.2 ± 0.4, p = 0.002; 4.4 ± 0.4 vs. 4.0 ± 0.5, p = 0.004). Conclusion: The acquisition and long-term retention of clinical skills within medical students are significantly greater when using immersive VR/AR training than traditional simulation methods. These findings help to support the integration of VR/AR modalities into medical education curricula to help improve clinical competency and student confidence. Keywords: Virtual Reality, Augmented Reality, Clinical Skills, Medical Education, Simulation Training, OSCE, Skill Retention, Immersive Learning